The Justice for Illegitimate Children of Indonesian Women Workers Through Constitutional Court Decision No. 46/PUU-VIII/2010 - Kusmayanti, Hazar; Kania, Dede; Rajamanickam, Ramalinggam; Masykur, Mohammad Hamidi (Jurnal IUS Kajian Hukum dan Keadilan, 2023)
The position of children out of marriage in everyday life by some people is seen as low, on the other hand in terms of welfare and civil rights still get limitations. This research focuses on the implementation of Constitutional Court Decision No. 46/ PUU-VIII /2010 on illegitimate children of Indonesian Women Workers. The research confirmed that the addition of Article 43 paragraph (1) made by the Constitutional Court through Decision No. 46/PUU-VIII/2010 is not only limited to the right to protection but has a very broad meaning that also includes illegitimate children born to Indonesian Women Workers. In accordance with the principle of equality before the law, the law must provide fair protection and legal certainty. The findings of this study revealed that illegitimate children of migrant workers can obtain constitutional rights as Indonesian citizens adhering to the principles of the rule of law. Therefore, the Constitutional Court’s decision does not only affect children’s inheritance rights, but also has implications for guaranteeing and protecting illegitimate children born to migrant workers, such as the right to earn a living, guardianship rights, and the right to get child support from a biological father.